Analisis Hukum Terhadap Timbulnya Panic Buying Bagi Masyarakat Berdasarkan Fatwa Majelis Ulama Indonesia Nomor 14 Tahun 2020 (Studi Kasus Kelurahan Indrapura Kecamatan Air Putih Kabupaten Batu Bara) - Nazlah Mardhiyah (ALWAQFU: Jurnal Hukum Ekonomi dan Wakaf, 2023)
This thesis is titled: "Legal Analysis of the Emergence of Panic Buying Amongst the Public Based on the Fatwa of the Indonesian Ulema Council No. 14 of 2020 (A Case Study of Indrapura Subdistrict in Air Putih, Batu Bara Regency). The implementation of panic buying by the residents of Indrapura Subdistrict involves people flocking to purchase health supplies such as masks, hand sanitizers, Bear Brand milk, health beverages like UC Vitamin 1000, and essential daily necessities such as cooking oil. This is done with the rationale of being prepared to stay at home as much as possible and stockpiling various provisions. The phenomenon of panic buying has become a significant issue that needs in-depth examination as it relates to certain prohibited transactions. The core research questions posed in this study are as follows: 1. How is panic buying conducted in the Indrapura Subdistrict of Air Putih, Batu Bara Regency, based on the Fatwa of the Indonesian Ulema Council No. 14 of 2020? 2. What are the factors contributing to the emergence of panic buying among the residents of Indrapura Subdistrict in Air Putih, Batu Bara Regency, as per the Fatwa of the Indonesian Ulema Council No. 14 of 2020? 3. What is the legal perspective on panic buying for the public, based on the Fatwa of the Indonesian Ulema Council No. 14 of 2020, in the Indrapura Subdistrict of Air Putih, Batu Bara Regency? 4. What is the author's analysis of panic buying among the residents of Indrapura Subdistrict in Air Putih, Batu Bara Regency? The aim of this research is to ascertain the legal standing of panic buying for the public, guided by the Fatwa of the Indonesian Ulema Council No. 14 of 2020. This empirical legal study employs a field research methodology, specifically utilizing the Living Case Studies Approach. Data collection involves observation, interviews, and document analysis. The conclusion drawn from this study is that the legal standpoint on the emergence of panic buying among the public, based on the Fatwa of the Indonesian Ulema Council No. 14 of 2020 (A Case Study of Indrapura Subdistrict in Air Putih, Batu Bara Regency), is that it is considered prohibited (haram). This is because the practice of panic buying does not conform to the principles of muamalah and falls into the category of prohibited transactions, potentially causing harm.